Особенности смешанных типов переноса металла при сварке в защитных газах длинной дугой - Пономарев, В.; Скотти, А. (Автоматическая сварка, 2005)
Проанализирована взаимосвязь вероятности появления смешанных типов переноса металла с динамическими характеристиками источника питания. Наблюдения за характером формирования и перехода капель осуществлялись с помощью установки, состоящей из лазера и высокоскоростной цифровой видеокамеры, при синхронной регистрации кривых напряжения дуги и тока сварки. Показано, что и в условиях сварки без коротких замыканий регулировка скоростей нарастания и снижения тока может существенно влиять на характер формирования и переноса капель и вызывать появление смешанных типов переноса металла. A mixed metal transfer mode in MIG/MAG welding, in which two or more transfer modes happen in a periodic sequence, is usually undesirable, because it may deteriorate the welding process stability. Thus, there is a strong appeal for investigating the causes of such a metal transfer mode in order to determine means of deal with this phenomenon. This work was aimed to make an experimental and descriptive analysis of the mechanisms that govern one of the free-flight metal transfer mixed mode in the MIG/MAG welding. For that, current rising and falling rates were systematically adjusted in an electronic power supply. The droplet formation and transfer were observed using an arc visualisation system based on a laser and a high-speed camera. The arc voltage and welding current signals were monitored, in synchronism with the droplet images (frames), using a computer-based measuring system. It was verified that one of the factors that provoke this mixed metal transfer mode is inadequate dynamic characteristics of the power source, namely, excessively fast current rising and falling rates that happen during welding circuit resistance changes caused by the metal droplet formation and detachment. The received results seem useful for electronic power source adjustments, as well as for designers of new welding power sources.